AN ENEMY TO FIGHT OR SOMEONE TO LIVE WITH, HOW COVID-19 IS METAPHORICALLY DESCRIBED IN INDONESIAN MEDIA DISCOURSE. - Adam, Muhammad (Proceedings of English Linguistics and Literature, 2020)
There are three stages in epidemic psychology, they are fear and panic, moralization, and action to be taken (Strong, 1990), those stages are often reflected in the discourse when communicating and reporting a pandemic. When Covid-19 started to spread at the early stage, all countries including online media channels describe the effort in handling the epidemic as if the Covid-19 is a war and an enemy to fight. But over time, there is a shift on how the Covid-19 is metaphorically described, especially when there is no significant decrease of the infected patients. Instead of describing it as an enemy, there is a tendency to view the Covid-19 as someone or something to live with. This study aims to examine the use of metaphor in describing Covid-19 as an enemy to fight and the Covid-19 as someone or something to accept and to live with. The war metaphor shows an optimism in reducing and controlling the disease, whereas the metaphor of someone or something to live with shows the tendency of pessimism in dealing with the Covid-19 spread and is frequently used at the later months. Conceptual Metaphor Theory (CMT) will be used as the theoretical background as it provides the framework to analyze metaphorical mapping. The study is qualitative and data will be taken from Indonesian online media news headlines that discuss the Covid-19 pandemic. The result shows that despite the pessimism entailments, the metaphor of FRIEND(SHIP) is far better in giving a positive image-schema particularly to ask people to live a new normal life with new healthy habits, whereas WAR metaphor will take people away from understanding the health issue. This study shall be an opening to further linguistics studies of Covid-19 discourse particularly in Indonesian context to contribute to the current issue worldwide.